KEBERADAAN BAHASA MELAYU-KUNA ABAD VII- IX C DI JAWA - Riboet Darmosoetopo (Berkala Arkeologi, 1998)
Inscriptions as cultural heritage and very important for use in writing history, are found throughout the Indonesian archipelago. However, the Old Malay-language inscriptions are only found in Sumatra and Java. Recently, an ancient Malay-language inscription was also found on the southern coast of the island of Laguna, Philippines. Eight Old Malay-language inscriptions from the Sriwijaya Kedatuan era were found in Sumatra. The eight inscriptions are the Kedukanbukit inscription (605 C), Talang Tuwo (606 C), Kota Kapur (608 C), Karangbirahi, Telaga Batu, Boom Baru, Palas Pasemah, and the Budulent inscription. The seven ancient Malay-language inscriptions found on the island of Java are Manjusrigrha (714 C), Payaman (700-750 C), Dapunta Selendra (± 750 C), Sang Hyang Wintang, Dang Pu Hawang Glis, Dewa Drawya (Dieng), and the inscription from Kebon Kopi. An inscription made of copper plates, in Old Malay, with Old Javanese script, dated 822 C was found on the coast of Laguna (South Philippine Islands). Problems arise about the existence of this Old-Malay language in Java, both regarding the process and its development in historical compilation. Therefore, in this small paper, we will try to propose the idea of ​​a solution even though it is still hypothetical.